INTRODUCTION OF NUCLEAR POWER PLANT FOR MITIGATING THE IMPACT OF GLOBAL WARMING - Ida Nuryatin Finahari (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2008)
ABSTRACTINTRODUCTION OF NUCLEAR POWER PLANT FOR MITIGATING THE IMPACT OF GLOBAL WARMING. Energy utilization for power plants in Indonesia is still highly depending on the burning of fossil fuel like coal, oil, and gas. From the combustion of fossil fuel, greenhouse gases such as CO2 and N2O are produced. An increase of CO2 gas emission to the atmosphere can block the heat loss from the earth surface and will increase the greenhouse effect that results in the temperature increase of the earth surface (global warming). Global warming can cause a very extreme climate change on earth. One of the solutions to reduce CO2 gas emission produced by fossil fuel power plants is to utilize the plants with flue gas treatment facility. At such facility, CO2 gas is reacted with certain mineral based substances thus can be used as base material in food-, pharmaceutical-, construction-, and cosmetic industry. Another alternative to reduce CO2 gas emission is by replacing fossil fuel power plants with nuclear power plants. Considering the environmental and economic aspects, the nuclear power plant does not emit CO2 gas, so that the use of nuclear power plant can mitigate the impact of global warming. Based on the operational experience of nuclear power plants in advanced countries, the cost of generating electricity from nuclear power plants is more competitive than that of fossil fuel power plant.Keywords: CO2 gas emission, global warming, climate change, fossil fuel power plant, nuclear power plant ABSTRAKINTRODUKSI PLTN UNTUK MENGURANGI DAMPAK PEMANASAN GLOBAL. Pemakaian energi di Indonesia untuk pembangkit listrik masih sangat bergantung pada pembakaran bahan bakar fosil seperti batubara, minyak bumi dan bahan bakar gas. Dari pembakaran bahan bakar fosil dihasilkan gas rumah kaca CO2 dan N2O. Adanya kenaikan laju emisi gas CO2 di udara dapat menghambat hilangnya panas dari permukaan bumi dan akan meningkatkan efek rumah kaca yang dapat menyebabkan naiknya suhu permukaan bumi (pemanasan global). Pemanasan global dapat mempengaruhi perubahan iklim yang sangat ekstrim di bumi. Salah satu upaya untuk mengendalikan laju emisi gas CO2 yang ditimbulkan dari pembangkit listrik berbahan bakar fosil adalah dengan melengkapi instalasi pengolahan gas buang pada unit pembangkit. Pada instalasi ini gas CO2 direaksikan dengan bahan mineral tertentu, yang dapat dimanfaatkan sebagai bahan baku pada industri makanan, farmasi, konstruksi dan industri kosmetik. Alternatif lain untuk mengurangi laju emisi gas CO2 adalah pemanfaatan energi nuklir (PLTN) untuk menggantikan pembangkit listrik berbahan bakar fosil. Ditinjau dari aspek lingkungan dan ekonomi, PLTN tidak mengeluarkan emisi gas CO2 sehingga dengan memanfaatkan PLTN dapat mengurangi dampak pemanasan global. Pengalaman pengoperasian PLTN di negara-negara maju menunjukkan bahwa biaya pembangkitan listrik PLTN cukup kompetitif dibanding pembangkit listrik berbahan bakar fosil.Kata kunci: emisi gas CO2, pemanasan global, perubahan iklim, pembangkit listrik berbahan bakar fosil, pembangkit listrik tenaga nuklir